Pioneers of Sino-Japanese Relations - Itoh, M. author. aut Link
XXII, 259 p.
Keywords: This book examines the careers of Liao Chengzhi and Takasaki Tatsunosuke, who were not only the architects of Sino-Japanese economic relations, but also pioneers of contemporary Sino-Japanese relations. Their visions and initiatives offer many insights into the current contentious relations among China, Japan, Russia, and the United States.